Transcranial direct current stimulation during a prolonged cognitive task: the effect on cognitive and shooting performances in professional female basketball players. Issue 4 (3rd April 2023) - Moreira, Alexandre; Moscaleski, Luciane; Machado, Daniel Gomes da Silva; Bikson, Marom; Unal, Gozde; Bradley, Paul S.; Cevada, Thais; Silva, Fabiana Tenório Gomes da; Baptista, Abrahão F.; Morya, Edgard; Okano, Alexandre Hideki
Abstract: The negative effect of prolonged cognitive demands on psychomotor skills in athletes has been demonstrated. Transcranial direct current stimulation (tDCS) could be used to mitigate this effect. This study examined the effects of tDCS over the left dorsolateral prefrontal cortex (DLPFC) during a 30-min inhibitory Stroop task on cognitive and shooting performances of professional female basketball players. Following a randomised, double-blinded, sham-controlled, cross-over design, players were assigned to receive anodal tDCS (a-tDCS, 2 mA for 20 min) or sham-tDCS in two different sessions. Data from 8 players were retained for analysis. Response Time decreased significantly over time ( p  < 0.001; partial η 2 = 0.44; no effect of condition, or condition vs. time interaction). No difference in mean accuracy and shooting performance was observed between tDCS conditions. The results suggest that a-tDCS exert no additional benefits in reducing the negative effects of prolonged cognitive demands on technical performance compared to sham (placebo). Practitioner summary: Prolonged cognitive demands can negatively affect the athletes' performance. We tested whether transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex (DLPFC) could attenuate these effects on cognitive and shooting performance in professional female basketball players. However, tDCS did not exert any additional benefits compared to sham. Abbreviations: tDCS: transcranial direct current stimulation; a-tDCS: anodal transcranial direct current stimulation; PFC: prefrontal cortex; DLPFC: dorsolateral prefrontal cortex; PCT: prolonged cognitive task; TT: time trial; RT: response time; NASA-TLX: National Aeronautics and Space Administration Task Load Index; RPE: ratings of perceived exertion; CR-10 scale: category rating scale; EEG: electroencephalogram; AU: arbitrary units.